MENINGKATKAN KEMAMPUAN FISIK MOTORIK HALUS ANAK MELALUI KEGIATAN MENGECAP DENGAN MENGGUNAKAN MEDIA PELEPAH PISANG USIA 5- 6 TAHUN DI TK BINA ANANDA - Sri Wahyuni; Endah Wahyu Sugiharti (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
The research is motivated by a problem of the low level of increasing children’s creativity through stamping activities using banana stems and media for group B at Bina Ananda Kindergarten. The type of research used is the classroom action research method which is  carried out in two cycles. The subjects in this study were group B students at Bina Ananda Kindergarten in the 2024/2025 Academic Year totaling 12 children, including 7 boys and 5 girls. The success criteria in this study are Developing According to Expectations (BSH) and Develoving Very Well (BSB). In cycle I only 6 children achieved the level of completion from a total of 12 children involved increasing stamping and increasing children’s creativity by 92%. The conclusion of the study is that the activity of stamping using banana stem media can increase the creativity of early childhood grop B at Bina Ananda Kindergarten. Keywords : Fine Motor Physical Ability, Stamping Activities, Early Childhood 5-6 Years.